Traffic-induced multicomponent ultrafine particle microphysics in the WRF v3.6.1 large eddy simulation model: General behaviour from idealised scenarios at the neighbourhood-scale. (15th February 2020) - Zhong, Jian; Nikolova, Irina; Cai, Xiaoming; MacKenzie, A. Rob; Alam, Mohammed S.; Xu, Ruixin; Singh, Ajit; Harrison, Roy M.
Abstract: Traffic is the key source of ultrafine particles (UFPs, particulate matter with a diameter less than 0.1 μm or 100 nm) in most urban areas. The traffic-generated UFPs vented out from an urban street mix with overlying 'urban background air' and are diluted whilst also undergoing change due to condensation/evaporation and other aerosol microphysics. Traffic-generated UFPs are comprised of a complex mixture of semi-volatile compounds (SVOCs) with volatility varying over many orders of magnitude, resulting in size-dependent particle composition. This study coupled the multicomponent microphysics (involving condensation/evaporation) of UFPs with the WRF v3.6.1 (Weather Research and Forecasting) large eddy simulation model (i.e. WRF-LES-UFP), and used this modelling system to investigate the general behaviour of UFPs on the neighbourhood scale (10-1000 m; transport times of few minutes) for idealised scenarios. The model captures the horizontal dispersion of UFPs downwind into the neighbourhood scale and vertical mixing with urban background air. Evaporation decreases the mode size of UFPs venting into the urban boundary layer from street-level. The neighbourhood-scale evolution of UFPs is, therefore, a combination of the effects of emissions, mixing with background, and condensation/evaporation. Total UFP number concentration and total mass concentrations scale linearly with the emission rate or the background concentration, demonstrating numerical conservation of the scheme. The linearity is less pronounced for the number concentration of smaller particles (UFP diameter less than 100 nm) with respect to UFP size and concentrations of those organic compounds with a time scale comparable to the dilution time scale (in the order of minutes), reflecting the effects (altering the particle sizes) due to condensation/evaporation. Graphical abstract: Image 1 Highlights: Multicomponent microphysics of UFPs is coupled with the WRF-LES model. General behaviour of UFPs on the neighbourhood scale dispersion is investigated. The combined effects of emissions, mixing and microphysics of UFPs are revealed.